An Overview of the Potentialities of Antimicrobial Peptides Derived from Natural Sources - Irene Dini; Margherita-Gabriella De Biasi; Andrea Mancusi (MDPI AG, 2022)
Antimicrobial peptides (AMPs) are constituents of the innate immune system in every kind of living organism. They can act by disrupting the microbial membrane or without affecting membrane stability. Interest in these small peptides stems from the fear of antibiotics and the emergence of microorganisms resistant to antibiotics. Through membrane or metabolic disruption, they defend an organism against invading bacteria, viruses, protozoa, and fungi. High efficacy and specificity, low drug interaction and toxicity, thermostability, solubility in water, and biological diversity suggest their applications in food, medicine, agriculture, animal husbandry, and aquaculture. Nanocarriers can be used to protect, deliver, and improve their bioavailability effectiveness. High cost of production could limit their use. This review summarizes the natural sources, structures, modes of action, and applications of microbial peptides in the food and pharmaceutical industries. Any restrictions on AMPs' large-scale production are also taken into consideration.